Insights into the role of PGF2α in canine periparturient myometrium - Jungmann, Carolin; Dyhrberg Haubuff, Signe; Packeiser, Eva-Maria; Körber, Hanna; Reichler, Iris Margaret; Balogh, Orsolya; Mazzuoli-Weber, Gemma; Goericke-Pesch, Sandra (Frontiers in Physiology, 2024)
Parturition in dogs is subjected to complex hormonal regulation with the involvement of prostaglandin F2α (PGF2α) still not being fully understood. To investigate uterine inertia (UI), the most prevalent maternal reason for dystocia in the bitch, a better understanding of undisturbed uterine and especially myometrial function is crucial. Our aim was to gain deeper insights into the role of PGF2α in the canine parturient myometrium. Uterine biopsies were obtained during medically indicated Cesarean sections. To test for stimulatory effects of PGF2α in vitro, circular and longitudinal myometrial layer tissue strips were challenged with 50 pM, 0.5 µM and 50 µM PGF2α. Prostaglandin-endoperoxide synthase 2 (PTGS2) and PGF2α-receptor (PTGFR) mRNA expressions were compared between primary UI (PUI) and obstructive dystocia (OD) samples in isolated parturient myometrium. PTGFR protein expression was assessed in full-thickness uterine samples. PGF2α concentrations were analyzed in canine interplacental tissue around term. In the organ bath, the contractile response to PGF2α was limited to the circular layer at the highest dosage. Correspondingly, PTGFR immunohistochemical staining was significantly stronger in the circular layer (p< 0.01). PTGS2 gene expression did not differ between PUI and OD, whereas PTGFR gene expression could not be quantified. Local uterine PGF2α concentrations correlated negatively with serum P4 levels and were highest during prepartum luteolysis while being significantly lower in PUI. Conclusively, despite the significant increase in local PGF2α concentrations in birth, confirming the interplacental tissue as production site, our results suggest that PGF2α might affect uterine contractility during labor mainly indirectly.